Evaluation of digital libraries : an insight into useful applications and methods - Papatheodorou, Christos; Tsakonas, Giannis (Chandos information professional series., 2009)
Evaluation of Digital Libraries summarizes research and practice on both sides of the Atlantic and aims to answer the potential questions that both the theoretical and practical areas of digital library evaluation have posed during recent years. The book systematically presents aspects of participating communities, reasons and aims of evaluation, methodologies and metrics, and application paradigms.